การปรับปรุงวัสดุหินผุเพื่อใช้เป็นวัสดุในงานพื้นทาง : กรณีศึกษาหินผุในเขตทางหลวงหมายเลข 11 จังหวัดอุตรดิตถ์ - ดุลยพล ชัยมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
It is widely known that construction materials for highway construction should meet Department of Highways standards. In Thailand, those materials are scarce in the Northern part; therefore, construction companies typically need to transport materials from other areas, resulting in a higher construction cost. This research aims to study the possibility of bringing weathered rock material in Uttaradit Province as base course. Such materials are subjected to preliminary tests for desired properties in terms of gradation, Atterberg Limit, California Baring Ratio (CBR), and Unconfined Compressive Strength (UCS). The stabilized materials are further tested for Resilient Modulus, and Durability Results show that stabilized materials in Uttaradit Province can satisfy the required standards. In addition, an economic analysis also reveals savings in terms of construction cost, comparing to the traditional usage of crushed rock in local area.